CHANGES IN THE LANDSCAPES OF THE FOOTHILLS AS A RESULT OF ANTHROPOGENIC IMPACT - Alimdjanov Nozimjon Nimadjanovich; Naimov Husniddin Nuriddin ugli (PEDAGOGS, 2025)
Foothill landscapes, transitional zones between lowland plains and mountainous regions, are characterized by diverse ecosystems, rich biodiversity, and unique geomorphological features. These areas are often subject to significant anthropogenic impacts due to their accessibility and resource availability. Human activities such as agriculture, urbanization, deforestation, and infrastructure development have profoundly altered these landscapes, leading to changes in soil composition, vegetation cover, and hydrological systems. This article examines the extent and nature of these changes, focusing on the ecological and geomorphological consequences of anthropogenic activities in foothill regions. The study aims to analyze the primary drivers of landscape transformation, assess their impacts, and discuss potential mitigation strategies.